Euro money market spreads during the 2007-? financial crisis - Nuno Cassola; Claudio Morana (European Central Bank (ECB), 2012)
In the paper we investigate the empirical features of euro area money market turbulence during the recent financial crisis. By means of a novel Fractionally Integrated Heteroskedastic Factor Vector Autoregressive model, we find evidence of a deterministic level factor in the EURIBOR-OIS (OIS) spreads term structure, associated with the two waves of stress in the interbank market, following the BNP Paribas (9 August 2007) and the Lehman Brothers (16 September 2008) "shocks", and two additional factors, of the long memory type, bearing the interpretation of curvature and slope factors. The unfolding of the crisis yielded a significant increase in the persistence and volatility of OIS spreads. We also find evidence of a declining trend in the level and volatility of OIS spreads since December 2008, associated with ECB interest rate cuts and full allotment policy.
Keywords: C32; E43; E58; G15; 330; credit/liquidity risk; fractionally integrated heteroskedastic factor vector autoregressive model; money market interest rates